The provenance signal of climate–tectonic interactions in the evolving St. Elias orogen: framework component analysis and pyroxene and epidote single grain geochemistry of sediments from IODP 341 sites U1417 and U1418 - Huber, Barbara; Bahlburg, Heinrich; Institut für Geologie und Paläontologie, Westfälische Wilhelms-Universität, Münster, Germany (International Journal of Earth Sciences, 2021)
The St. Elias orogen and the Surveyor Fan in the adjacent Gulf of Alaska are a coupled source to sink system recording the interplay of tectonics and variable degrees of glaciation during the collision of the Yakutat terrane with the southern Alaska margin since the Miocene. The Miocene to Holocene sediments of the Surveyor Fan were drilled during IODP expedition 341. The recovered material is used to constrain information on changes in erosion centers during the last 10 Ma to study the impact of climatic and tectonic processes on orogen evolution. Point counting of sand- and silt-sized light framework components and geochemical single grain analysis of heavy mineral groups epidote and pyroxene is applied to analyze patterns of sedimentary provenance of two sites on the distal and proximal Surveyor Fan (Site U1417 and U1418, respectively). The studied sands and silts of Miocene to Pleistocene age are slightly enriched in feldspar (plag >> kf) at the proximal site, compositions at both sites do not show systematical changes with time of deposition. Framework component spectra uniformly reflect the expected active margin provenance. Epidote and pyroxene compositions are very consistent and show no change with time of deposition. Associations of epidote and pyroxene with albite, titanite and pumpellyite are in line with near-shore sources in the Chugach Metamorphic Complex and the metabasite belt at its southern border, and in units of recycled detritus exposed in the fold and thrust belt on the western Yakutat Terrane, respectively. Rock fragments indicate input from mainly metamorphic sources during the Miocene and Pliocene and an increase of input from low-grade metamorphic and sedimentary rocks in the Pleistocene, a finding also indicated by the abundance of epidote and pyroxene. This implies increasing erosion of the near-shore areas of the fold and thrust belt with advance of glaciers to the shore since the Miocene, being enhanced by the onset of the Northern Hemisphere glaciation at the beginning of ...